Integrative transcriptomic and proteomic analyses reveal a positive role of BES1 in salt tolerance in Arabidopsis - Feng, Lei; Li, Yan; Zhou, Yu-Ling; Meng, Guang-Hua; Ji, Zhao-Lin; Lin, Wen-Hui; He, Jun-Xian (Frontiers in Plant Science, 2023)
Introduction Salt stress is a major environmental factor limiting plant growth and development. Previous studies have indicated that the steroidal hormones—brassinosteroids (BRs) are important regulators of plant responses to salt stress. However, the underlying molecular mechanisms have not been fully understood. Methods (1) Phenotypic analysis of bes1-D, BES1-RNAi and their wild-type (Col-0) under salt treatments with different concentrations of NaCl. (2) Transcriptomic and proteomic profiling of BES1-regulated genes and proteins under salt treatment; (3) qRT-PCR validation of selected BES1-regulated genes under salt stress; (4) Transient transcriptional assay of BES1 regulation on its putative target genes in Arabidopsis protoplasts; (5) Electrophoresis Mobility Shift Assay (EMSA) of BES1 binding with its potential target genes. Results and Discussion Phenotypic analysis indicated that bes1-D, a gain-of-function mutant of the BR-regulated transcription factor BES1 in Arabidopsis showed better salt tolerance than the wild-type plant, while a BES1 RNA interference (BES1-RNAi) line was more sensitive to salt stress. Global gene expression profiling and time series clustering analyses identified a total of 1,170 genes whose expression was boosted in bes1-D under salt stress. Further GO enrichment and gene functional network analyses identified several key modules that are regulated by BES1 and most sensitive to salt stress perturbations, including stress response, response to ABA and ROS, flavonoid biosynthesis and transmembrane transport. A comparative proteomic analysis performed under the same stress conditions supported the results from the transcriptome analysis. In addition, transient gene transcription assays in Arabidopsis protoplasts and in vitro DNA binding assays verified that BES1 regulates the expression of some ion transporter genes directly and indirectly. Taken together, our results support a positive role of BES1 in plant salt tolerance.